2011
DOI: 10.1002/ibd.21442
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of mucosal and submucosal colonic tissues yields protein signatures that differentiate the inflammatory colitides

Abstract: BACKGROUND Differentiating ulcerative colitis (UC) from Crohn's colitis (CC) can be difficult and may lead to inaccurate diagnoses in up to 30 percent of inflammatory bowel disease (IBD) patients. Much of the diagnostic uncertainty arises from the overlap of clinical and histologic features. Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) permits a histology-directed cellular protein analysis of tissues. As a pilot study, we evaluated the ability of histology-directed MALDI-MS to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 35 publications
0
74
0
Order By: Relevance
“…A few proteomics studies using biopsies and PBMCs from Crohn's disease patients have been published (42)(43)(44). The heterogeneity of these samples makes it impossible to characterize the individual T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A few proteomics studies using biopsies and PBMCs from Crohn's disease patients have been published (42)(43)(44). The heterogeneity of these samples makes it impossible to characterize the individual T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Han et al [34] identified a large number of differentially expressed proteins (37 relevant for CD, 27 for UC and 11 associated with general IBD) that were seen as candidate biomarkers. M'koma and colleagues conducted two studies that identified spec tral peaks representing unknown protein profiles and reported being able to accurately distinguish between the UC and CD using an algorithm [35,36] . These tissue findings however are likely to require validation in plas 30 February 15, 2016|Volume 7|Issue 1| WJGP|www.wjgnet.com…”
Section: Pre-clinical Presentationmentioning
confidence: 99%
“…Normal colon: 3 M'koma et al [35] Colon samples CD: 27 Histology directed MALDI-TOF 5 m:z peaks were identified and cross-validated for the differentiation of UC and CD UC: 24 Seeley et al [36] Colon samples CD: 26 Histology directed MALDI-TOF Using a support vector machine and 25 m:z peaks, UC and CD cases were predicted in 93.3% and 60.4% respectively. A lower spectral accuracy cut-off increased sensitivity UC: 36…”
Section: -Dementioning
confidence: 99%
“…A wide selection of proteomic approaches has been applied to characterize IBD pathogenesis by investigating the dynamic nature of the proteome 41 , including surface-enhanced laser desorption ionization (SELDI) or matrix-assisted laser desorption (MALDI)-time of flight (TOF) mass spectrometry (MS) and liquid chromatography (LC/MS) combined with two-dimensional gel electrophoresis. Such proteomic studies have been performed for IBD using epithelial cell lines [42][43][44] , epithelial cells from colonic biopsies [45][46][47] and serum samples [48][49][50][51] . Currently, the greatest interest in proteomic applications lays in identifying biomarkers in biofluids (such as serum and urine) or tissue samples (such as colonic biopsies) 41 that are specific for UC and CD diseases and correlate with disease activity and other clinicopathological parameters.…”
Section: Revealing the Ibd Proteomementioning
confidence: 99%